Research on Integration Application of Virtual Simulation Technology and Vocational Education Teaching - Xu, Jiada (Journal of Theory and Practice of Social Science, 2024)
With the continuous development and progress of the Times, the teaching method of vocational education has changed greatly. At the same time, there are some problems in the teaching of vocational education. At present, due to the limitation of school environment, some vocational schools do not have enough space for students to carry out practical learning. In order to break through the limitation caused by environment, schools can use virtual simulation technology instead of practical teaching. This paper mainly analyzes the problems existing in vocational education teaching, and discusses and studies the integration of virtual simulation technology and vocational education. The new normal in the era of "Internet plus" can optimize the practice of entrepreneurship and alleviate the bad mood of college students at the same time. Contemporary college students pay more attention to new things, with the development of "Internet plus", they will look forward to using new tools to carry out innovative entrepreneurial activities, thereby meeting the needs of social development. In addition, college students can also combine the "Internet plus" with new entrepreneurial thinking, to lay a solid foundation for the practice of entrepreneurship.